2007
DOI: 10.1007/s11676-007-0045-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sensor quantity on measurement accuracy of log inner defects by using stress wave

Abstract: Wood nondestructive testing (NDT) is one of the high efficient methods in utilizing wood. This paper explained the principle of log defect testing by using stress wave, and analyzed the effects of sensor quantity on defect testing results by using stress wave in terms of image fitting degree and error rate. The results showed that for logs with diameter ranging from 20 to 40 cm, at least 12 sensors were needed to meet the requirement which ensure a high testing accuracy of roughly 90% of fitness with 0.1 of er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Sometimes the anthropogenic actions are so severe that they affect the integrity and even the stability of the trees, especially in the case of trees located in the cities, near the road, which are cut extremely intensively. In contrast to trees from forests managed for production, whose management is aimed at getting high quality wood for various industrial uses (Sandoz and Lorin 1996;Garrett 1997;Wang et al 2007;Mu et al 2010;Du et al 2015;Qu et al 2020;Lin and Wu 2013;Sandak et al 2020), for urban trees the main aim is to maintain their vitality, integrity, and stability for as long as possible (Kirkpatrick et al 2012;Camacho-Cervantes et al 2014;Sandoz and Lorin 1996;Deflorio et al 2008;Wang et al 2009). Initially, the condition of a tree and its maintenance or removal was decided by a single person, who visually evaluated it (van Wassenaer and Richardson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the anthropogenic actions are so severe that they affect the integrity and even the stability of the trees, especially in the case of trees located in the cities, near the road, which are cut extremely intensively. In contrast to trees from forests managed for production, whose management is aimed at getting high quality wood for various industrial uses (Sandoz and Lorin 1996;Garrett 1997;Wang et al 2007;Mu et al 2010;Du et al 2015;Qu et al 2020;Lin and Wu 2013;Sandak et al 2020), for urban trees the main aim is to maintain their vitality, integrity, and stability for as long as possible (Kirkpatrick et al 2012;Camacho-Cervantes et al 2014;Sandoz and Lorin 1996;Deflorio et al 2008;Wang et al 2009). Initially, the condition of a tree and its maintenance or removal was decided by a single person, who visually evaluated it (van Wassenaer and Richardson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The application and propagation rules of SWT were studied by detecting defects in trees and assessing the safety conditions of trees (Wang et al, 2007). The number of sensors can influence the fit and error rate of stress wave images, at least 12 sensors are needed to make the image fit close to 90%, and the error rate is reduced to 0.1 (Wang, Xu & Zhou, 2007). Study has indicated that the relationship between stress waves and resistance values was significant (Allison & Wang, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors influence the quality of the acoustic and ultrasonic images [10]. The number of sensors, for example, is directly related to the spatial resolution of the image; a larger number of sensors allows a smaller defective area detection [11,12]. The excitation signal used for testing is directly related to the precision of the TOF estimation, affecting the image reconstruction method [13,14].…”
Section: Introductionmentioning
confidence: 99%